2017
DOI: 10.1109/lra.2017.2679902
|View full text |Cite
|
Sign up to set email alerts
|

A Continuum Robot and Control Interface for Surgical Assist in Fetoscopic Interventions

Abstract: Twin–twin transfusion syndrome requires interventional treatment using a fetoscopically introduced laser to sever the shared blood supply between the fetuses. This is a delicate procedure relying on small instrumentation with limited articulation to guide the laser tip and a narrow field of view to visualize all relevant vascular connections. In this letter, we report on a mechatronic design for a comanipulated instrument that combines concentric tube actuation to a larger manipulator constrained by a remote c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 23 publications
(25 reference statements)
0
33
0
Order By: Relevance
“…This will require to develop robust underwater registration methods adapted to intended applicative context (e.g learning-based approaches) or combine it with robotic imaging [8]. It will also be interesting to evaluate such a framework for deep underwater imaging as [2] observed that the thin refractive plane assumption well approximate for thick refractive interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This will require to develop robust underwater registration methods adapted to intended applicative context (e.g learning-based approaches) or combine it with robotic imaging [8]. It will also be interesting to evaluate such a framework for deep underwater imaging as [2] observed that the thin refractive plane assumption well approximate for thick refractive interface.…”
Section: Resultsmentioning
confidence: 99%
“…The interface to camera centre distance along the camera's axis is denoted as d. An image point i observed in view j is denoted p [2,2], [2,4], [3,5], [4,3], [4,7], [5,6], [5,8], [6,9]) = 1.…”
Section: Rt Water Refractive Interfacementioning
confidence: 99%
“…This limits the camera motion to only 4DoF (3 in rotation and 1 in translation) and results in illconditioned hand-eye constraints. While a possible solution would be to allow a surgical robot to freely move in 6DoF during a calibration phase, this is neither practical nor possible for mechanisms with mechanical RCM implementations [3]. However, as we will show in this paper, it is possible to take advantage of the RCM constraints to improve hand-eye calibration for such robot configurations.…”
Section: Trocar Pointmentioning
confidence: 99%
“…The schematic shows a magnified version of the type of movement of the camera when being used in RMIS. RCM is denoted at the trocar point to minimise a chance of a robot arm damaging the surrounding tissues [2], [3]. The camera motion is restricted around the RCM and this provides a very small motion range which is not sufficient for a decent calibration.…”
Section: Trocar Pointmentioning
confidence: 99%
“…With the reduction in size, complex actuation systems are required. Long kinematic chains (12 active joints in the da Vinci robot [5], Intuitive Surgical, USA), micro-machined super-elastic tool guides with pneumatic artificial muscles [6] and concentric tubes [7] are recent examples of these highly complex actuation mechanisms. As a consequence, the kinematics of such robotic manipulators become less stable due to hysteresis, friction and backlash.…”
Section: Introductionmentioning
confidence: 99%